2021
DOI: 10.3390/molecules26206289
|View full text |Cite
|
Sign up to set email alerts
|

Rooibos Flavonoids, Aspalathin, Isoorientin, and Orientin Ameliorate Antimycin A-Induced Mitochondrial Dysfunction by Improving Mitochondrial Bioenergetics in Cultured Skeletal Muscle Cells

Abstract: The current study investigated the physiological effects of flavonoids found in daily consumed rooibos tea, aspalathin, isoorientin, and orientin on improving processes involved in mitochondrial function in C2C12 myotubes. To achieve this, C2C12 myotubes were exposed to a mitochondrial channel blocker, antimycin A (6.25 µM), for 12 h to induce mitochondrial dysfunction. Thereafter, cells were treated with aspalathin, isoorientin, and orientin (10 µM) for 4 h, while metformin (1 µM) and insulin (1 µM) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Mangiferin is a xanthone present in significant levels in higher plants and possesses a variety of pharmacological actions, including anticancer, antidiabetic, antioxidative, immunomodulatory, hepatoprotective, analgesic, and neuroprotective effects [ 69 , 70 ]. Orientin is a water-soluble flavonoid C-glycoside with antioxidant, antiaging, antiviral, antibacterial, anti-inflammation, vasodilatation and cardioprotective, antiadipogenesis, antinociceptive, radiation-protective, neuroprotective, and antidepressant-like effects [ 71 , 72 , 73 , 74 ]. CB2R was also reported to be involved in the regulation of inflammation, anti-cancer, anti-fibrotic, and nerve system disease [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mangiferin is a xanthone present in significant levels in higher plants and possesses a variety of pharmacological actions, including anticancer, antidiabetic, antioxidative, immunomodulatory, hepatoprotective, analgesic, and neuroprotective effects [ 69 , 70 ]. Orientin is a water-soluble flavonoid C-glycoside with antioxidant, antiaging, antiviral, antibacterial, anti-inflammation, vasodilatation and cardioprotective, antiadipogenesis, antinociceptive, radiation-protective, neuroprotective, and antidepressant-like effects [ 71 , 72 , 73 , 74 ]. CB2R was also reported to be involved in the regulation of inflammation, anti-cancer, anti-fibrotic, and nerve system disease [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, injection with the isoflavone puerarin, at 100 mg/kg for 4 weeks, could downregulate the expression of a range of genes involved in mitochondrial biogenesis and oxidative phosphorylation, such as PGC-1α, NRF1/2, and transcription factor A (TFAM) in HFD-fed Wistar rats [ 13 ], whereas treatment with HFD containing the phenylpropanoid chicoric acid, at 0.03%, w/w for 6 weeks, was associated with improved glucose and insulin metabolism, while also reversing mitochondrial biogenesis and oxidative phosphorylation within the skeletal muscle in C57BL/6 mice fed HFD for 10 weeks [ 34 ]. Collaboratively, our group has increasingly reported on the potential therapeutic effects of bioactive compounds with abundant antioxidant effects, including polyphenols which are highly present in fruits and vegetables, in improving skeletal muscle function by ameliorating insulin resistance and targeting improving mitochondrial function [ 58 , 59 ].…”
Section: Therapeutic Interventions That Affect Skeletal Muscle Functi...mentioning
confidence: 99%
“…Secondly, rooibos constituents quercetin, aspalathin and catechin inhibit lipid peroxidation ( Snijman et al, 2009 ), a mechanism likely responsible for its reported membrane-protective effects of rooibos ( Ulicna et al, 2019 ; Pretorius and Smith, 2022 ). A multitude of studies in cell-free systems and in cell culture have also demonstrated improved antioxidant enzyme activities (particularly for catalase and superoxide dismutase (SOD)) ( Waisundara and Hoon, 2015 ) and mitochondrial bioenergetics ( Mthembu et al, 2021 ).…”
Section: Rooibos: Doomed To Fail or On The Road To Success?mentioning
confidence: 99%